COGNITIVE FEATURES OF TERMS - Zhusupov, N.; Shakhmetova, N.; Bekbosynova, A.; Baratova, M. (European Scientific Journal, ESJ, 2013)
﻿﻿In this paper, on the material of the Kazakh and Russian languages is determined by the cognitive nature of terms. In the paradigm of cognitive terminology the term is understood as information and cognitive structure, accumulating special knowledge needed in the process of scientific communication and professional and scientific activity. Terms as mental representations have the following characteristics: reflect the results of cognitive human activity, scientific way of thinking, are the means of knowledge of reality, a factor of particular social importance, as they reflect the needs of society in a particular scientific information. More or fewer number of terms representing the analyzed subject group is determined by the role that animals perform in the life of a particular people.